Characterization of HIV-1 subtype B near full-length genome sequences identified at the start of HIV epidemic in South Africa - Obasa, Adetayo Emmanuel (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMedSc)--Stellenbosch University, 2017.